PEMBENTUKAN CITRA POSITIF AKADEMI ANGKATAN LAUT MELALUI LATIHAN PRAKTEK PELAYARAN KARTIKA JALA KRIDA (Universitas Negeri Surabaya, 2021)
In an institution or agency, image is an important and high value asset. A good image is very important and must be owned by any institution to determine the success of an institution in developing programs. In military institutions, good or bad image is very important, because military institutions play a direct role in serving the community. One of the military institutions that upholds imaging is the Naval Academy (AAL). Based on this, this research is intended to find out the strategy carried out by the Naval Academy (AAL) to build a positive image. This research was conducted using an observational qualitative approach by conducting interviews with related parties. The results showed that in the mission of forming a positive image, AAL has various supporting programs, namely the Kartika Jala Krida (KJK) special practical training program (Lattek). In addition, it is also carried out by carrying out diplomatic missions that aim to introduce Indonesian culture to the international world. Keywords: Image, Naval Academy (AAL). KJK Technical Training.